1990
DOI: 10.1016/0020-7292(90)90005-6
|View full text |Cite
|
Sign up to set email alerts
|

Anamnestic pregnancy risk assessment

Abstract: Based on data obtained from the 1984-1985 Guadeloupean Perinatal Audit, a pregnancy risk scoring system was developed using maternal demographic, socioeconomic, obstetric history and risk characteristics recorded at the first prenatal visit. Various combinations of risk factors were identified for four distinct pregnancy outcomes (perinatal mortality, low birth weight, preterm delivery and intra-uterine growth retardation). The findings emphasize the importance of developing risk assessments for discrete pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Several other retrospective analyses attempted to associate perinatal mortality with the presence of specific risk factors. In Guadeloupe, West Indies, using data from the 1984–85 Guadeloupean Perinatal Audit, de Caunes et al [ 17 ] observed that perinatal mortality was associated with a specific combination of risk factors representing maternal demographic, socioeconomic, obstetric history and risk characteristics measurable at the first antenatal visit, leading the authors to advocate for risk assessments specific to pregnancy outcomes within specific populations [LOE: 3-] .…”
Section: Resultsmentioning
confidence: 99%
“…Several other retrospective analyses attempted to associate perinatal mortality with the presence of specific risk factors. In Guadeloupe, West Indies, using data from the 1984–85 Guadeloupean Perinatal Audit, de Caunes et al [ 17 ] observed that perinatal mortality was associated with a specific combination of risk factors representing maternal demographic, socioeconomic, obstetric history and risk characteristics measurable at the first antenatal visit, leading the authors to advocate for risk assessments specific to pregnancy outcomes within specific populations [LOE: 3-] .…”
Section: Resultsmentioning
confidence: 99%
“…Die m ü tterlichen Parameter K ö rpergr ö ß e und K ö rpergewicht haben ebenfalls einen Einfl uss auf die Fr ü hgeborenenraten [9] . Anhand fr ü herer epidemiologischer Studien gab es Versuche, Risiko-Scores zum Vorhersagewert einer Fr ü hgeburtlichkeit zu ermitteln [6,7,10,12,19,21,23,28] . Ein signifi kanter Zusammenhang zwischen Anamnese und einer erh ö hten Fr ü hgeborenenrate konnte z.…”
Section: Introductionunclassified
“…Of the 16 studies that included model development, five studies collected data prospectively (Allouche et al, 2011; Gioan et al, 2018; Mercer et al, 1996; Misra et al, 2001; Zhu et al, 2017), 10 studies collected data retrospectively (Baer et al, 2018; de Caunes et al, 1990; Goyal et al, 2015; Hueston, 1998; Lee et al, 2020; Luo et al, 2016; Morken et al, 2014; Tan et al, 2007; Weber et al, 2018; Woolery, 1992), and one study combined prospective and retrospective designs (Takagi et al, 2012). Of the five studies that only conducted validation, three studies collected data prospectively (R. K. Creasy et al, 1980; Goodfellow et al, 2019; Holbrook et al, 1989), one study collected data retrospectively (Edenfield et al, 1995), and one study combined both designs (Wilson & Sill, 1973) (Table 2).…”
Section: Resultsmentioning
confidence: 99%